1983
DOI: 10.1203/00006450-198310000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Urogastrone and Lactose Concentrations in Precolostrum, Colostrum, and Milk

Abstract: SummaryThe concentration of urogastrone (URO) and lactose was measured in breast secretions from four women. URO levels were high in precolostrum and fell markedly around the time of parturition to relatively constant low levels in mature milk. When milk samples were fractionated on a Biogel PI0 column, the major peak of immunoreactivity occurred at the point at which pure URO eluted.There was good correspondence between the fall in URO levels at birth and the increase in lactose levels, suggesting that the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…High concentrations of EGF are present in human colostrum and milk [83][84][85] and in nipple aspirates [86]. The concentration of EGF in plasma is extremely low [87,88] but increases during pregnancy [89], suggesting that EGF may have a role in breast differentiation.…”
Section: The Presence Of Growth Factors In Hbcfmentioning
confidence: 97%
“…High concentrations of EGF are present in human colostrum and milk [83][84][85] and in nipple aspirates [86]. The concentration of EGF in plasma is extremely low [87,88] but increases during pregnancy [89], suggesting that EGF may have a role in breast differentiation.…”
Section: The Presence Of Growth Factors In Hbcfmentioning
confidence: 97%
“…Furthermore, it is not certain at what level EGF may exert some of these effects, because some effects noted in the intact animal are not found in intestinal culture studies, suggesting that the intestinal EGF effects may be part of a systemic response to EGF (45). In the present study, EGF was added to the explant medium at a concentration that approximates the upper limit of the concentration in human colostrum (49). At this concentration, EGF significantly stimulated total protein synthesis in the piglet jejunal explants.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have measured the concentration of EGF in human milk, bovine milk and bovine milk-based infant formulae (11)(12)(13)(14)(15)(16)(17)(18). Human milk contains a high concentration of EGF in comparison with other tissues or body fluids.…”
Section: Regional Differences In Egf Concentrationmentioning
confidence: 99%
“…Human milk contains a high concentration of EGF in comparison with other tissues or body fluids. However the concentration of EGF in human milk varied among the various studies because of differences in measuring methods: radioreceptor assay (RRA, 15,16,17,18,20) and radioimmune assay (RIA,11,12,14). Even by RRA, Iacoptta et al reported that when placental plasma membrane is used for RRA the concentration of EGF might be overestimated, whereas intact A431 cells are used this does not happen.…”
Section: Regional Differences In Egf Concentrationmentioning
confidence: 99%
See 1 more Smart Citation